STUDY OF COLLAGEN IV INDICATORS IN URINE BEFORE AND AFTER TREATMENTS IN PATIENTS WITH HEPATORENAL SYNDROME WITH LIVER CIRRHOSIS OF VIRUS ETIOLOGY (HEPATITIS B AND C) (World Bulletin of Public Health, 2022)
Cirrhosis of the liver is manifested by necrosis of hepatocytes, disruption of its normal architecture due to diffuse growth of connective tissue and the formation of regeneration nodules, as well as progressive fibrosis. The article presents a modern approach to the treatment of hepatorenal syndrome, one of the severe complications of the disease. The effect of eplerenone, Lornithine L-aspartate and glutathione drugs on kidney fibrosis was evaluated based on complex treatment